Pengaruh Penghindaran Pajak dan Egoisme Psikologis Terhadap Kinerja Pendapatan Perpajakan - Vidayanti, Riska; Askandar, Noor Shodiq; Malikah, Anik (Universitas Islam Malang, 2024)
Tax revenue is the main source of income for the Indonesian state in financing development programs and improving people's welfare. However, tax avoidance and the phenomenon of psychological egoism are serious challenges that plague the tax system. This research aims to identify the influence of tax avoidance and psychological egoism on the tax revenue performance of individual taxpayers at KPP Pratama Batu. The research method used is quantitative analysis by collecting primary data through questionnaires distributed to individual taxpayers. The collected data was analyzed using descriptive statistical techniques and regression to test the research hypothesis. The research results show that tax avoidance has a positive and significant impact on the gap between prospective and actual tax collection, while psychological egoism has a negative and significant impact on revenue collection. The implications of these findings support the need for more effective policies in reducing tax avoidance and increasing public tax awareness to achieve the goals of optimal tax revenue and sustainable social development.Keywords: Tax avoidance, tax, evasion, psychological egoism, tax revenue performance